A language of things : Emanuel Swedenborg and the American environmental imagination - Zuber, Devin P., 1978- (Studies in religion and culture (Charlottesville, Va.), 2019)
"This book considers the fundamental role that religious experience at times played in shaping nineteenth-century American approaches to natural space. By tracing the ways that Ralph Waldo Emerson, John Muir, Sarah Orne Jewett, and Vachel Lindsay all variously responded to the philosophy and theosophy of Emanuel Swedenborg, Zuber illuminates the complex dynamic that came to unfold between the religious, the literary, and the ecological"--